ANALISIS TINGKAT LIKUIDITAS PT. BAKRIE SUMATERA PLANTATIONS TBK PADA TAHUN 2012-2016 - Bulan, Matilda - (EKONOMIA, 2019)
ABSTRACTAnalysis of the level of liquidity of PT. Bakrie Sumatera Plantations TBK in 2012-2016 (under the guidance of Mrs.Mardiana as supervisor I and Mr. Sarwo Eddy Wibowo as supervisor II). This study generally aims to determine the level of liquidity of PT. Bakrie Sumatera Plantations Tbk in 2012-2016. Specifically this study aims to find out and analyze the current financial ratio of PT. Bakrie Sumatera Plantations Tbk. In the period 2012-2016. To find out and analyze the financial cash ratio of PT. Bakrie Sumatera Plantations Tbk in the period 2012-2016. To find out and analyze the financial quick ratio of PT. Bakrie Sumatera Plantations Tbk in the period 2012-2016.Data analysis used by the writer in this final project report is quantitative descriptive method. The data used in this study were obtained from the Indonesia Stock Exchange (IDX) by downloading via the website www.idx.co.id for the 2012-2016 period and other sources related to this research. Calculation steps in the level of liquidity at PT. Bakrie Sumatera Plantations Tbk, carried out an analysis of the current ratio, cash ratio, and quick ratio in each period of 2012-2016, then searched for a mean value for 5 years.The results of the study revealed that the level of liquidity at PT. Bakrie Sumatera Plantations Tbk in the 2012-2016 period is still below the industry average liquidity standard of 200% for the current ratio, 50% for the cash ratio, and 150% for the quick ratio. And the results of this study are not in accordance with the hypothesis which states that PT. Bakrie Sumatra Plantations Tbk was able to achieve the industry average liquidity standard in the 2012-2016 period. The value of the current ratio in 2012 was 126.24%, in 2013 was 54.40%, in 2014 was 33.73%, in 2015 was 18.37%, in 2016 was 9.86%. The average current ratio for 5 years is 48.52%. The 2012 cash ratio is 4.02%, in 2013 it was 1.84%, in 2014 it was 0.72%, in 2015 it was 0.54%, in 2016 it was 0.59%. The average cash ratio for 5 years is 1.54%. The quick ratio value in 2012 was 118.22%, in 2013 it was 51.83%, in 2014 it was 31.98%, in 2015 was 16.54%, in 2016 it was 8.90%. The average quick ratio value for 5 years is 45.49%.The conclusion of this study is, the average industry standard of liquidity that is still below does not mean the company lacks capital in running its business, considering that in this study only use the three most commonly used financial ratios and do not use all liquidity ratios to analyze financial statements. PT. Bakrie Sumatera Plantations Tbk still has the opportunity to increase its liquidity in the years to come.Â Â